2019
DOI: 10.1139/apnm-2018-0430
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress, inflammation, psychological status, and severity of respiratory infections are negatively affected during the pre-contest period in amateur bodybuilders

Abstract: We examined whether off-season (OffS) and pre-contest (PreC) periods affect blood oxidative stress, inflammatory, immunological, and psychological markers in 20 bodybuilders. The athletes recorded their food intake (3-day record), physical activities, mood states (Profile of Mood States, POMS), recovery-stress (Recovery–Stress Questionnaire for Athletes, RESTQ-Sport), and upper respiratory symptoms (Wisconsin Upper Respiratory Symptom Survey, WURSS-21), and blood was obtained for biochemical analysis. Almost a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 36 publications
0
14
0
1
Order By: Relevance
“…Observational evidence may also indicate that some athletes choose to maintain high loads, decreasing the training volume, while using some sets near to failure, and with intraset rest intervals due to fatigue and tiredness induced by severe caloric restriction. The weeks before competing also involve protocols to induce dehydration and a very low carbohydrate intake, which may also contribute to these training strategies [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Observational evidence may also indicate that some athletes choose to maintain high loads, decreasing the training volume, while using some sets near to failure, and with intraset rest intervals due to fatigue and tiredness induced by severe caloric restriction. The weeks before competing also involve protocols to induce dehydration and a very low carbohydrate intake, which may also contribute to these training strategies [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…It plays an essential role in the pathophysiology of various complications of DM as well as viral respiratory disorders [ 51 54 ]. In addition to damaging various biological molecules in the respiratory tract, this pathologic milieu initiates and progresses other molecular mechanisms involved in respiratory infections such as uncontrolled apoptosis or necrotic processes [ 53 , 55 ]. Using antioxidant supplements could sometimes help as adjuvant therapy for the management of certain respiratory infections [ 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…The same strategy of negative energy balance occurs in other sport disciplines associated with pre-contest periods, such as in Taekwondo ( Rhyu et al, 2014 ). Such strategies might initiate negative mood alterations, autonomic deregulation, compromised force-generating capacity, as well as elevations in cortisol and reductions in testosterone levels ( de Moraes et al, 2019 ). Moreover, the pre-contest period might induce damage to cell components and greater severity of upper respiratory tract infections from an increase of inflammatory mediators and pro-oxidant markers ( Fry et al, 2008 ).…”
Section: Anabolic Steroids Ergogenic Substances and Blood Flow Restri...mentioning
confidence: 99%
“…Recently, a study showed that severe restriction energy intake during the pre-contest period was associated with an increase in oxidative stress markers (TBARS, malondialdehyde and protein carbonyls), impaired upregulation of antioxidant enzymes (glutathione reductase, catalase activity, and superoxide dismutase), and decreased plasma total antioxidant capacity ( Rhyu et al, 2014 ; de Moraes et al, 2019 ). Moreover, a previous study revealed that during the pre-contest preparation period, different strategies (AS, clenbuterol, thyroid hormone, and ephedrine) might result in maladaptive effects on the lipid profile and alteration of transaminases, increasing the atherosclerotic heart disease risk and liver dysfunction ( de Souza et al, 2018 ).…”
Section: Anabolic Steroids Ergogenic Substances and Blood Flow Restri...mentioning
confidence: 99%